Integration of the Values of Independence and Creativity through Practical Learning in Islamic Junior High Schools - Yayuk Sukraningsih; Siti Mudlikah (Agrapana Media, 2026)
The implementation of independence and creativity values at MTs Al Yakin Pungpungan has not been optimally realized through classroom theory alone, so structured practical activities are needed to strengthen students’ character in cognitive, affective, and psychomotor aspects. This study aims to analyze the integration of the values of independence and creativity independence and creativity values through the practice of making clothing fragrances at MTs Al Yakin Pungpungan using a Project-Based Learning (PjBL) approach. This research is a field case study with data collection techniques through participatory observation, in-depth interviews, and documentation. The results of the study show that project activities are able to increase students' active involvement, build responsibility, and foster creativity in designing products and packaging. Students not only understand the production process technically, but also learn to make decisions and work together in groups. In addition, this project provides contextual experiences that are relevant to real life and nurtures awareness of the economic value of products. These findings affirm that project-based learning is effective in developing independent and creative character in junior high school students.